E01 Analysis of mitochondrial genes as potential genetic modifiers of the age-at-onset in Huntington disease. (29th August 2012) - Brauner, H; Metzger, S; Riess, O; Nguyen, HP
Abstract : Background: The major determinant of age-at-onset (AAO) in Huntington disease (HD) is the length of the causative polyglutamine expansion in the huntingtin protein, which is inversely correlated with the AAO and the course of the disease. However, both environmental and genetic factors are thought to modify the disease. Here, genetic factors are proposed to have an essential influence and especially polymorphism in genes associated with HD pathogenesis are thought to act as genetic modifiers. One characteristic feature in HD pathogenesis is mitochondrial dysfunction, which is marked by an impairment of mitochondrial integrity and trafficking leading to a disruption of mitochondrial function and an inhibition of energy supply in the cell. Amongst others, mutant huntingtin was shown to lead to oxidative stress, increased fragmentation of mitochondria and reduced ATP levels. A regulated expression of proteins, involved in mitochondrial fission and fusion (eg, Mfn1, Mfn2) antagonises the pathogenic effect, thus demonstrating to be interesting potential candidates for a modifying role in HD. Aim/method: In order to identify genetic modifiers participating in mitochondrial function, we investigated several single nucleotide polymorphisms in mitochondrial fusion (Mfn1, Mfn2, Opa1) and fission (Fis1) genes for their frequency of ≥1%. Subsequently, we aim to analyse these polymorphic markers for a disease-modifying effect in more than 1400 European HD patients. Additionally, to establish a connection between mutant huntingtin and mitochondrial genes, we intend to examine a possible interaction between huntingtin and the fission protein Fis1 by co-immunoprecipitation experiments in cell culture. Conclusion: The present study provides the opportunity to identify new genetic modifiers influencing the AAO and the pathogenic course of HD. These would further support the important pathophysiological role of mitochondrial dysfunction in HD and may offer new basis for further clarification of HD pathology.